A Study on Zero Offset Uncertainty on CMP 6 Pyranometer - Adhikari, Krishna Raj (Journal of Nepal Physical Society, 2017)
This paper presents the zero offset in CPM6 pyranometer installed in Pokhara. In a pyranometer, a negative output called zero offset is observed when inner dome has a different temperature from the sensor and there is a net loss of energy by the pyranometer dome to the colder atmosphere which in turn is compensated by the sensor. This offset occurs due to thermal exchanges and temperature gradient within the instrument is often referred to as a zero offset, one of the uncertainties, because it becomes apparent at times when the signal should be zero. In this study, it is found that the variation of the uncertainty is independent of the day length but varies specially with climatic/weather conditions (cloud cover, wind speed, air temperature, etc) of that particular day, month, season and location. Commonly, two negative maxima were found every day; one associated with early morning hour (before sunrise) and another with evening/night before 24 hours (after sunset). Journal of Nepal Physical Society Volume 4, Issue 1, February 2017, Page: 111-118